Effect of the blade shaped by Joukowsky airfoil transformation on the characteristics of the torque converter. (December 2021) - Pan, Xiong; Xinyuan, Chen; Hongjun, Sun; Jiping, Zhong; Lin, Wu; Huichao, Gao
Cavitation is common in traditional torque converters whose blades are designed by beam theory; the blade curvature is discontinuous and cannot be analysed by functions. In this paper, the YJH265 torque converter is used as the prototype to reconstruct the stator blades with Joukowsky airfoil transformation. Computational Fluid Dynamics (CFD) is used analyse the flow field in the torque converter with the three-dimensional transient full flow channel. Combined with experiments, cavitation is found at the exit of the YJH265 torque converter stator. This is the same as the cavitation position of different torque converters studied by other scholars, and the flow state at the simulation outlet is high vacuum, boundary layer separation and high turbulent kinetic energy. Without changing the angle and chord length, the stator blades were reshaped and simulated with the optimised Joukowsky airfoil. As a result, the boundary layer separation phenomenon disappeared, the vacuum degree and turbulent kinetic energy were reduced, the torque ratio increased by 0.175 (5.6%), and the efficiency increased by 4.9%. To conclude, the optimised Joukowsky airfoil can be used in the design of stator blades, and its streamline is consistent with the fluid dynamics characteristics, which greatly reduces the probability of cavitation and improves the performance and service life of the torque converter.